Lactoperoxidase is a candidate for mediating neuromelanin formation in the human substantia nigra - Zsuzsanna E. Tóth; Mónika Baráth; Veronika F. S. Pape; Klaudia Sípos; Adél P. Boros; Máté Durst; Péter Várnai; Gábor Sirokmány; Miklós Geiszt (Proceedings of the National Academy of Sciences, 2026)
The presence of neuromelanin is a characteristic feature of the human substantia nigra (SN); however, the mechanism of its synthesis and its role in the development of Parkinson’s disease remain unclear. Here, we report that the host defense enzyme lactoperoxidase (LPO), which possesses broad antimicrobial activity on mucosal surfaces, is selectively expressed in human dopaminergic neurons, a feature not shared by the rodent SN. We also demonstrate that LPO can catalyze multiple steps of melanin formation in vitro, and transgenic expression of human LPO in the rat SN induces the appearance of neuromelanin. Based on our results, LPO likely contributes to neuromelanin formation in the SN. Since LPO degrades H 2 O 2 during neuromelanin synthesis, the enzyme’s activity represents a previously unrecognized link between neuromelanin formation and antioxidant defense mechanisms.